Hungarian Monitoring, 24 August 1990 . [Magyar rádiófigyelő], 1990. augusztus 24 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - 61 countries keep Kuwaiti embassies open - Soviet Union evacuates its embassy building in Kuwait - Soviet-French foreign ministers' talks on the Gulf crisis - Romanian refugees in Czechoslovakia - Kohl's visit to Berlin - Slovak nationalists prepare to declare an independent Slovakia - Rescheduling of Polish debts Domestic Affairs: - Antall receives Ukrainian foreign minister Zlenko - Iraqi soldiers surround Hungarian foreign representation - Debating the privatization law Economy: - Mercury poisoning in Kazincbarcika - Situation of the Nagykőrös Conserve Factory - List of drought damage Külpolitika: - 61 ország nem számolja fel kuvaiti nagykövetségét - A Szovjetunió evakuálja kuvaiti nagykövetségét - Szovjet-francia külügyminiszteri tárgyalás az öbölválságról - Román menekültek Csehszlovákiában - Kohl látogatása Berlinben - Szlovák nacionalisták önálló Szlovákia kikiáltására készülnek - Lengyelország adósságainak átütemezése Belpolitika: - Antall fogadja Zlenko ukrán külügyminisztert - Iraki katonák körbezárták a magyar külképviseletet - Privatizációs törvény vitája Gazdaság: - Higanyszennyezés Kazincbarcikán - A Nagykőrösi Konzervgyár helyzete - Aszálykárlista